Photobiomodulation Modulates Proliferation and Gene Expression Related to Calcium Signaling in Human Osteoblast Cells: Photobiomodulation effects in human osteoblasts - Bomfim, Fernando Russo Costa do; Sella, Valéria Regina Gonzalez; Thomasini, Ronaldo Luis; Plapler, Hélio (Journal of Lasers in Medical Sciences, 2024)
Introduction: Photobiomodulation with low-level laser treatment can enhance bone formation by stimulating the cell division of osteoblasts and increasing the amount of protein deposition, thus encouraging the formation of new bone. This study aimed to evaluate the effects of photobiomodulation with a low-level laser on proliferation and gene expression related to calcium signaling in human osteoblasts. Methods: Osteoblastic cell lines of the hFOB1.19 lineage, human osteoblasts, were grown and assigned into two groups, control (C; n=78 cultured wells) and photobiomodulation (L; n=78 cultured wells) with n=6 per day of the experimental period. Cells were cultured (immature at 34 ºC), and after maturation at 37 ºC, group L cells were exposed to laser irradiation with a low-level laser device (gallium and aluminum arsenide), at a wavelength of 808 nm, a power output of 200 mW, and a power density of 200 mW/cm2. The energy delivered to the cells was 37 J/cm2, with a beam area of 0.02 mm2 and an exposure time of 5 seconds. This treatment was applied daily for 13 days. Following this, the number of cells was counted, and RNA was isolated, measured, and then converted into cDNA for further quantification using a comparative Ct method with real-time polymerase chain reaction. The results were then subjected to statistical analysis through a Mann-Whitney test, with a significance level of P<0.05. Results: The cell count in the L group (37.25x10±4±22.02) was statistically higher compared to the control group (22.75x10±4±7.660) with a P value of 0.0259. The values of 2- ΔΔCt for S100A6, plasma membrane calcium ATPase (PMCA), and calmodulin genes indicated hyperexpression on the thirteenth day, while the osteocalcin gene showed hypo-expression. Conclusion: The study suggests that the photobiomodulation mechanism with a low-level laser may regulate gene expression in human osteoblasts in a dose-dependent and cumulative manner.